2008
DOI: 10.1007/s10658-008-9287-0
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural factors affecting Verticillium wilt in olive orchards in Spain

Abstract: In recent years, the spread of Verticillium wilt in olive orchards, caused by the soil-borne pathogen Verticillium dahliae, is often related to intensive modern farming of highly productive cultivars, planted at high densities, usually irrigated, and under a mechanised system. The effects of agricultural factors associated with olive orchards were investigated in an important olive-growing area in southern Spain, as tools in predicting outbreaks of the disease. A stratified double-sampling technique was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…In this case, early studies showed that the D pathotype was localized in marsh areas of the Lower Guadalquivir Valley (Southern Spain), where cotton was intensively grown (Bejarano-Alcázar et al 1995). From that well-defined area, a steady dispersal of the D pathotype to new, distant olive cultivation regions has been reported (Mercado-Blanco et al 2003;Navas Cortés et al 2008;Rodríguez et al 2008). It is tempting to suggest the existence of similar scenarios where the same factors (i.e., previous susceptible crops, changes from dry-farming to irrigation, very susceptible cultivars, use of infected planting material, etc.)…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this case, early studies showed that the D pathotype was localized in marsh areas of the Lower Guadalquivir Valley (Southern Spain), where cotton was intensively grown (Bejarano-Alcázar et al 1995). From that well-defined area, a steady dispersal of the D pathotype to new, distant olive cultivation regions has been reported (Mercado-Blanco et al 2003;Navas Cortés et al 2008;Rodríguez et al 2008). It is tempting to suggest the existence of similar scenarios where the same factors (i.e., previous susceptible crops, changes from dry-farming to irrigation, very susceptible cultivars, use of infected planting material, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…While infections by the D pathotype can be lethal to the plant, olive plants infected with the ND pathotype can recover from symptoms (Rodríguez-Jurado 1993;Jiménez-Díaz et al 1998;Mercado-Blanco et al 2001). In Europe, natural infections by the D pathotype have been only reported in Spain (López-Escudero and Blanco-López 2001;Mercado-Blanco et al 2003;Navas Cortés et al 2008;Rodríguez et al 2008) and Western Turkey (Dervis et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although irrigation regime, nitrogen fertilization, plant and weed density, planting date and depth, and previous cropping history are known to be important factors affecting FRR development and bean production (Abawi and Widmer 2000;Brien et al 1991;Burke and Miller 1983;Deibert 1995;Kraft et al 1981), regional assessment of the various agronomic factors linked to FRR at different growth stages is not well documented. Although there have been a number of large-scale investigations describing the associations between agricultural and disease variables (Fernandez et al 2007;Fininsa and Yuen 2001;Rodríguez et al 2008;Sahile et al 2008;Workneh et al 1999;Zewde et al 2007), only a few large-scale studies have explored agronomic indicators of yield reductions in pathosystems (Mila et al 2003). Furthermore, the substantial differences in FRR and yield levels observed between adjacent fields with similar soil and climatic characteristics (Naseri and Marefat, unpublished data) encouraged us to focus on common agricultural operations recommended by local experts and growers to be effective for FRR control and bean yield.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, increasing irrigation dosages in crops or an inadequate irrigation schedule have been identified as cultural practices favouring Verticillium wilt onset and severity in a number of crops, such as potato (Arbogast et al 1999), tomato, cotton (Huisman and Grimes 1989;Blanco-López and De Vay 1987), and olive (Blanco-López et al 1984;AlAhmad and Mosli 1993;Serrhini and Zeroual 1995;Rodríguez et al 2008). Nevertheless, in other hosts, such as cauliflower, this effect is not clear and may even be contradictory (Xiao and Subbarao 2000).…”
mentioning
confidence: 99%